2016
DOI: 10.1038/cddis.2016.324
|View full text |Cite
|
Sign up to set email alerts
|

Functional KCa1.1 channels are crucial for regulating the proliferation, migration and differentiation of human primary skeletal myoblasts

Abstract: Myoblasts are mononucleated precursors of myofibers; they persist in mature skeletal muscles for growth and regeneration post injury. During myotonic dystrophy type 1 (DM1), a complex autosomal-dominant neuromuscular disease, the differentiation of skeletal myoblasts into functional myotubes is impaired, resulting in muscle wasting and weakness. The mechanisms leading to this altered differentiation are not fully understood. Here, we demonstrate that the calcium- and voltage-dependent potassium channel, KCa1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…We investigated two other members of the FHL family, named FHL2 and FHL3 during skeletal muscle cell development, and found that FHL2 promotes myogenic differentiation in C2C12 cells (Liu et al, 2019), but FHL3 inhibits satellite cells differentiation into myotubes in chicken (Han et al, 2019a). weakness, and atrophy occur when the fusion of mononucleated myoblasts into functional myotubes suffers damage (Tajhya et al, 2016). Previous studies have reported defects in muscle fiber structure and mass due to the absence of FHL1.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated two other members of the FHL family, named FHL2 and FHL3 during skeletal muscle cell development, and found that FHL2 promotes myogenic differentiation in C2C12 cells (Liu et al, 2019), but FHL3 inhibits satellite cells differentiation into myotubes in chicken (Han et al, 2019a). weakness, and atrophy occur when the fusion of mononucleated myoblasts into functional myotubes suffers damage (Tajhya et al, 2016). Previous studies have reported defects in muscle fiber structure and mass due to the absence of FHL1.…”
Section: Discussionmentioning
confidence: 99%
“…The α subunit of KCa1.1 was detected in RA‐FLSs by trypsinizing the cells, permeabilizing with 0.5% saponin, and staining with an anti‐KCa1.1 α antibody (Supplemental Table S2), followed by Alexa Fluor 488 fluorophore‐conjugated secondary antibody (Thermo Fisher Scientific), as described elsewhere (15, 16, 20). For analysis of total and activated β 1 ‐integrin expression levels, 1 × 10 4 FLSs were plated onto fibronectin‐coated 24‐well plates in the presence of 20 μM paxilline or DMSO for 1 h. Cells were detached from the plates using cell lifters, then stained for integrins using fluorophore‐conjugated antibodies; clone MAR4 for total β 1 integrins, clone HUTS21 for activated β 1 integrin, clone 7.2R for α 4 integrin, clone 238307 for α 5 integrin, or clone GoH3 for α 6 integrin (Supplemental Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…In human cardiac fibroblasts, BKCa inhibition by paxilline results in a cell proliferation reduction [20]. Recently, it was reported that blocking of KCa1.1 in normal myoblasts induced an increase in proliferation [6], suggesting that regulation of cell proliferation by BKCa channels may be celltype dependent. Recently, it was reported that blocking of KCa1.1 in normal myoblasts induced an increase in proliferation [6], suggesting that regulation of cell proliferation by BKCa channels may be celltype dependent.…”
Section: Discussionmentioning
confidence: 99%
“…BKCa channels are involved in the modulation of vasomotor and nerve excitability by regulating membrane potential and calcium signalling [3]. It strongly impacts physiological cell functions, for example, in human primary skeletal myoblast [6] or in pathologies such as obesity and brain, prostate, and mammary cancers [2]. Interestingly, increasing evidence indicates that the channel plays a key role in numerous biological processes such as cell metabolism, proliferation, migration, and gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation